The potency of minerals to reduce oriental fruit fly infestation in chili fruits - Pangihutan, Josua Crystovel; Dono, Danar; Hidayat, Yusup (PeerJ, 2022)
Introductions In many areas, particularly in Asia, the oriental fruit fly Bactrocera dorsalis (Hendel) causes considerable fruit damage on various plants. The fruit fly causes significant economic losses every year due to reduced fruit quantity and quality as well as export restrictions. This study aimed to examine the potency of minerals in controlling the oriental fruit fly infestation in chili fruits. Methods Experiments were conducted under laboratory and semi-field conditions using randomized block design. Ten minerals (i.e. kaolin, talc, zinc oxide, bentonite, sulfur, dolomite, calcium oxide, calcium hydroxide, calcium carbonate, and zeolite) and an untreated control were tested under laboratory conditions. Twenty chili fruits at a green stage were soaked in each mineral suspension (2%, w/v), air-dried, and placed in a trial cage (23-L plastic container) containing 20 female oriental fruit flies. In a semi-field bioassay using a screen cage (100 cm × 70 cm × 120 cm), 20 female oriental fruit flies were exposed to a fruit-bearing chili plant sprayed with mineral suspension. Results Talc and calcium oxide significantly reduced the numbers of visiting fruit flies, oviposition holes, and eggs laid, as well as the percentage of infested chili fruits in a laboratory bioassay. Calcium hydroxide was substantially better than talc in controlling fruit fly infestation in a semi-field bioassay, although it was not significantly different from calcium oxide and calcium carbonate. Conclusion Overall, calcium oxide is a viable option for the long-term control of the oriental fruit fly on chili fruits. Calcium oxide could be utilized as the push component of a push-pull strategy to manage oriental fruit fly infestation in chili fruits because of its potential to inhibit the number of visiting fruit flies and oviposition.
Keywords: Particle film; Fruit fly control; Bactrocera dorsalis; CaO; Natural pesticide